2019
DOI: 10.1093/advances/nmy105
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Milk and Other Dairy Products on the Risk of Frailty, Sarcopenia, and Cognitive Performance Decline in the Elderly: A Systematic Review

Abstract: Nutrition is a modifiable factor potentially related to aging. Milk and other dairy products may contribute to the prevention of physical and cognitive impairment. We conducted a systematic review to investigate the effectiveness of dairy product intake for preventing cognitive decline, sarcopenia, and frailty in the elderly population. A systematic search for publications in electronic databases [MEDLINE via PubMed, Embase, Scopus, the Cochrane Central Register of Controlled Trials (CENTRAL), and the Cochrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
66
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(73 citation statements)
references
References 65 publications
4
66
0
3
Order By: Relevance
“…Milk and other dairy products may contribute to the prevention of physical and cognitive impairment [ 36 ]. Our study found that milk and dairy products intake was positively correlated with higher scores for FP1, which had beneficial effect on cognitive function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Milk and other dairy products may contribute to the prevention of physical and cognitive impairment [ 36 ]. Our study found that milk and dairy products intake was positively correlated with higher scores for FP1, which had beneficial effect on cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that milk and dairy products intake was positively correlated with higher scores for FP1, which had beneficial effect on cognitive function. However, in older Japanese individuals a significant inverse relation between dairy intake and the development of AD was found [ 36 ]. A longitudinal study suggested no significant association between consumption of dairy products and MCI in French women [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…As shown by different studies, on average, the prevalence of sarcopenia in older adults aged 60–70 years lies at 5–13%, increasing to 11–50% in people aged 80 or older . Sarcopenia is closely related to negative outcomes in older adults, such as an increased risk of falls and fractures and impaired cognitive function and physical performance . These factors further lead to the negative clinical outcomes and socio‐economic consequences, such as poor quality of life and higher overall health care cost .…”
Section: Introductionmentioning
confidence: 99%
“…whey) or isolated nutrients (e.g. leucine) and less is known about the role of whole foods rich in protein, such as milk and milk products, in sarcopenia [9,10]. Incorporating foods dense in nutrients beneficial for ageing muscle [11] within a balanced diet may inform the development of strategies to mitigate sarcopenia that are acceptable to older adults [12], and not reliant on nutritional supplements or pharmacotherapy.…”
Section: Introductionmentioning
confidence: 99%